COOPERATION OF SCHOOL, FAMILY AND NEIGHBORHOOD IN EDUCATION OF SPIRITUAL THINKING OF YOUNG STUDENTS - Nusratov Anvar Ne’matjonovich (PEDAGOGS, 2024)
Abstract: In this article, the school educates the spiritual thinking of students and the role of public cooperation in society, school and community tasks of cooperation, methods of education based on pedagogical cooperation is talked about.